1996
DOI: 10.1016/0197-4580(96)00026-7
|View full text |Cite
|
Sign up to set email alerts
|

Trace eyeblink conditioning in rabbits demonstrates heterogeneity of learning ability both between and within age groups

Abstract: conditioning in rabbits demonstrates heterogeneity of learning ability both between and within age groups. NEUROBIOL AGING 17(4) 619-629, 1996.-Rabbits 2 to 41 months of age were conditioned in the 500 ms trace eyeblink paradigm to cross-sectionally define the age of onset and the severity of age-associated impairments in acquisition of this relatively difficult hippocampally dependent task. Using a strict behavioral criterion of 80% conditioned responses (CRs), age-associated learning impairments were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 57 publications
7
101
2
Order By: Relevance
“…It was shown that physiological reductions of I AHP increased the stability of stored patterns, whereas large increases reduced the correlation between network output and the stored pattern, i.e., memory and the recall of that memory (Berner, 1991). Such observations are intriguing because reduced AHPs have been observed in CA1 neurons in vitro after learning and because enhanced AHPs have been observed in CA1 neurons from aged animals (Landfield and Pitler, 1984;Moyer et al, 1992;Disterhoft et al, 1994a) that are significantly impaired in many learning tasks, including trace eyeblink conditioning (Thompson et al, 1996a). Another model based on empirical data demonstrated how general increases in postsynaptic excitability coupled with presynaptic, pathwayspecific modulation can prevent storage of incoming information from interfering with recall of previously formed associations (Hasselmo and Bower, 1993).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…It was shown that physiological reductions of I AHP increased the stability of stored patterns, whereas large increases reduced the correlation between network output and the stored pattern, i.e., memory and the recall of that memory (Berner, 1991). Such observations are intriguing because reduced AHPs have been observed in CA1 neurons in vitro after learning and because enhanced AHPs have been observed in CA1 neurons from aged animals (Landfield and Pitler, 1984;Moyer et al, 1992;Disterhoft et al, 1994a) that are significantly impaired in many learning tasks, including trace eyeblink conditioning (Thompson et al, 1996a). Another model based on empirical data demonstrated how general increases in postsynaptic excitability coupled with presynaptic, pathwayspecific modulation can prevent storage of incoming information from interfering with recall of previously formed associations (Hasselmo and Bower, 1993).…”
Section: Discussionmentioning
confidence: 90%
“…Subjects were New Zealand albino rabbits (Oryctolagus cuniculus), purchased from Hazelton rabbitry (Denver, PA), and maintained in accordance with guidelines established by the USDA and approved and managed by Northwestern University's Animal Care Committee. Rabbits received 500 msec trace eyeblink conditioning or pseudoconditioning as described previously (Moyer et al, 1990;Thompson et al, 1992Thompson et al, , 1996a. Briefly, rabbits were fitted with restraining headbolts and trained in pairs in individual sound-attenuated chambers for daily 80 trial sessions (mean intertrial interval, 45 sec).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SCRs were slightly larger on unperceived trace CS than on unperceived trace CS trials, and perhaps significant differences would have been observed had it not been for other factors that can influence conditioning. For example, trace procedures appear to be more difficult than delay conditioning, and increasing task difficulty often interferes with CR acquisition (Carter et al, 2003;Solomon & Groccia-Ellison, 1996;Thompson, Moyer, & Disterhoft, 1996). In addition, the duration of the trace CS was shortened to maintain the same interstimulus interval between CS onset and UCS presentation for the delay and trace procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In this paradigm, each trial consists of a neutral auditory conditioned stimulus (CS) followed by a stimulus free trace period, then a nonnoxious eyeblink-eliciting airpuff unconditioned stimulus (US) presented to the cornea. After repeated trials, young animals and humans learn to associate the CS and US, whereas a subset of aged animals and humans show poor learning on this task (Finkbiner and Woodruff-Pak 1991;Thompson et al 1996;Woodruff-Pak et al 1999). This ability to separate aging-impaired from -unimpaired subjects has made trace eyeblink conditioning a very effective tool in animal and human research on aging.…”
Section: Introductionmentioning
confidence: 99%